(untitled) (Cinema: Journal of Philosophy and the Moving Image, 2014)
This fifth issue of Cinema: Journal of Philosophy and the Moving Image is entirely dedicated to philosophy and Portuguese cinema, with a particular focus on the philosophical perspectives about its motion pictures. We took, as our starting point, the awareness that, although the studies with this kind of focus are scarce (and brief), centred primarily on the works of Pedro Costa and Manoel de Oliveira, the majority of Portuguese films have a strong connection with philosophical inquiry. This particular encounter is revealed in a unique aesthetic, but also in a complex network, determined by circumstances of the recent political, cultural and social history, which marked Portuguese cinema at a political, ethical, aesthetic and cultural level. With this issue, we aim at helping to fulfil this gap, contributing to the philosophical inquiry on Portuguese cinema, taken here in its broadest sense, i.e., including feature films, documentary films and trends in video art. We have tried to broaden the already established dialogue between filmmakers and philosophers, widening the scope of the aesthetic- philosophical analysis to meet the disciplinary intersection of historical, political and psychoanalytic readings, also crossing intermediatic approaches to the moving image that include such disparate creators as Paul Rocha, Miguel Gomes, Alberto Seixas Santos, António da Cunha Telles, Solveig Nordlund, José Álvaro Morais, Manuel Goncalo Mozos, opening the scope to other protagonists of the moving image in our country, such as Vasco Araújo, João Onofre or Filipa César.